Language education and emotions research into emotions and language learners, language teachers and educational processes - Simons, Mathea; Smits, Tom F. H. (Routledge Research in Language Education Series, 2021)
Language Education and Emotions presents innovative, empirical research into the influence of emotions and affective factors in language education, both in L1 and in foreign language education. It offers a comprehensive overview of studies authored and co-authored by researchers from all over the world. The volume opens and ends with "backbone" contributions by two of the discipline's most reputed scholars: Jane Arnold (Spain) and Jean-Marc Dewaele (United Kingdom). This book broadens our understanding of emotions, including well-known concepts such as foreign language anxiety as well as addressing the emotions that have only recently received scientific attention, driven by the positive psychology movement. Chapters explore emotions from the perspective of the language learner and the language teacher, and in relation to educational processes. A number of contributions deal with traditional, school-based contexts, whereas others study new settings of foreign language education such as migration. The book paints a picture of the broad scale of approaches used to study this topic and offers new and relevant insights for the field of language education and emotions. This book will be of great interest to academics, researchers and postgraduate students in the field of language education, psycholinguistics, sociolinguistics, and applied linguistics.